The Effect of Workload and Stress on Performance with Job Satisfaction as an Intervening Variable - Kartika Indrawati; Eko Hariyanto; Azmi Fitriati; Hengky Widhiandono (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of workload and stress on employee performance with job satisfaction as an intervening variable. This study was conducted at PT Tumbakmas Niagasakti in the Central Java area, Indonesia. The research method used is quantitative, with primary data collection through questionnaires using Google Forms. Of the 191 respondents who met the criteria, 170 respondents (89%) provided valid data. Data analysis was conducted using Statistical Product and Service Solutions (SPSS). The results showed that workload and stress have a positive effect on performance and job satisfaction. Other results show that, in addition to job satisfaction having a positive effect on performance, job satisfaction is also proven to mediate the relationship between workload and stress on performance. These findings can be a reference for management to manage workload and stress to improve employee satisfaction and performance.